Implementation of Salam Contract in Sharia Contract Farming Model for the Welfare of Poor Farmers in Indonesia (Equilibrium: Jurnal Ekonomi Syariah, 2025)
Limited access to capital remains a structural problem for poor farmers. This study aims to explore the potential implementation of the Salam contract in a sharia contract farming scheme as a solution to limited access to capital for poor farmers and provide recommendations for its implementation based on comprehensive data. The data used are secondary data from available literature and the 2024 National Socioeconomic Survey (Susenas). Data were analyzed using descriptive statistical methods and literature studies. The results of this study indicate that the population working in the agricultural and plantation sectors reached 34.89 million people. There are 1.85 million poor farmers (9.26 percent) in the rice and secondary crops farming sector, 340.37 thousand poor farmers (7.29 percent) in the horticulture sector, and 601.68 thousand poor farmers (5.88 percent) in the plantation sector. More than 50 percent of farmers are aspiring middle-class residents who are highly vulnerable to falling into the vulnerable and poor classes. In terms of access to capital, only 4.71 percent of farmers have People's Business Credit (KUR). Access to other financial institutions, such as Rural Credit Banks (BPR), cooperatives, or alternative financing sources such as Village-Owned Enterprises (BUMDes), does not reach 1 percent. From the demand side, the largest consumption is rice, reaching nearly 22 million tons with a value of IDR 303.56 trillion, followed by kale (1.05 million tons), spinach (882.4 thousand tons), tomatoes (586.32 thousand tons), and shallots (8 million tons). The sharia contract farming model based on the salam contract can strengthen the bargaining power of poor farmers, who are still weak. Implementation can be carried out through two pilot project approaches: in areas with the highest number of poor farmers or for food commodities with high demand and sales value